Interdisciplinary full‐mouth rehabilitation for redefining esthetics, function, and orofacial harmony. Issue 3 (4th January 2019) - Edelhoff, Daniel; Probst, Florian; Ehrenfeld, Michael; Prandtner, Otto; Schweiger, Josef; Liebermann, Anja
Abstract: Objective: In severe congenital or acquired orofacial anomalies, both dental esthetics and function are usually compromised. In particular, the esthetic ideas of the final desired appearance may differ from patient to patient, as the human esthetic sensibility differs significantly. Especially in complex cases, digital technology today offers outstanding improvements and simplifications in craniomaxillofacial surgical and prosthetic treatments, leading to a wide range of planning and pretreatment options. Clinical Considerations: This case report describes a patient‐oriented interdisciplinary craniomaxillofacial surgical and prosthetic treatment with noninvasive tooth‐colored splints, a Le Fort I osteotomy, and a full‐mouth rehabilitation to meet the patient's demand for better function as well as orofacial esthetics and harmony. Conclusions: By means of the digitally planned Le Fort I intervention and completion of the prosthetic rehabilitation, it was possible to optimize esthetics and facial harmony. Clinical Significance: In complex cases, digital technology today offers outstanding improvements and simplifications in craniomaxillofacial surgery and prosthetic treatments, leading to a wide range of planning and pretreatment options. Computer‐aided design/computer‐aided manufacturing technology enables the fabrication of tooth‐colored flexible polycarbonate splints that offer a noninvasive, removable, functional, and esthetic solution. In intricate cases involving craniomaxillofacial anomalies, often together with necessary orofacial surgeries or prosthetic treatments due to moderate to severe tooth wear, such digital preprosthetic treatment and planning options represent an important enhancement with more predictable results.